Oral acitretin treatment in severe congenital ichthyosis of the neonate - Saraçoğlu, Z. Nurhan; Tekin, Neslihan; Ürer, Selim M.; Sabuncu, İlham; Akşit, Arif (The Turkish Journal of Pediatrics, 2002)
Two newborn infants with ichthyosis, one with lamellar ichthyosis and one with nonbullous ichthyosis form erythroderma, who presented at birth with a collodion baby appearance, were treated with acitretin (1 mg/kg/day). Clinical improvement was achieved shortly after treatment. The second case received oral retinoid for 3.5 months and was followed for nine months. The result was excellent. The treatment resulted in a satisfactory improvement in the skin condition of the first case. The tolerance to the drug was good. Side effects were not observed. It was concluded that early management of severe ichthyosis cases could prevent life-threatening events such as hyperthermia, disturbance in electrolyte and fluid balance, and infection.
Keywords: congenital ichthyosis; collodion baby; acitretin; retinoids